Review State Administrative Law On The Duties And Authority Of The Lurah In The Matter Of The Making Of E-KTP (Study In Padang Matinggi Lestari Village, Padang Sidimpuan City) - Bobby Asyer (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2020)
In an effort to realize good village governance, the application of the principles contained in Good Governance is very important. Through the main tasks and authority of the lurah in coordinating and being responsible for the administration of government, implementation of development and community development in the context of administering general government and regional government affairs in his working area and is obliged to organize his own household in the field of village administration. The problems studied in writing this thesis are, How is the general overview of the Village Government and E-KTP, How is the E-KTP made as a form of public service, what are the obstacles faced in making E-KTP in Padang Matinggi Lestari Village, Padangsidimpuan City. The method used in this legal research is normative juridical based on related books, which are then analyzed qualitatively and described in words.The implementation of the E-KTP or electronic identity card in the Padang Matinggi Village, Padang sidimpuan City, is part of the principle of good governance in public services. The village head is more dominant in running the government in his working area. The population document is for administrative control in terms of an information security system based on integrated database technology that collects population data on a national scale. because there will only be one resident identification number in each electronic identity card (E-KTP).The obstacles faced in making the E-KTP in the Padang Matinggi Sustainable Village, Padang sidimpuan City, among others: There are still many residents of the Padang Matingg Sustainable Village who have not been registered and the community does not understand the procedure for making E-KTP. Human resources are not yet ready. Especially the Padangsidimpuan Village Government area in the implementation of making E-KTP so that people wait too long and lack the facilities needed when the policy is implemented.